Agronomic, physiological and transcriptional characteristics provide insights into fatty acid biosynthesis in yellowhorn (Xanthoceras sorbifolium Bunge) during fruit ripening - Liu, Guan; Liu, Fengjiao; Pan, Lin; Wang, Hanhui; Lu, Yanan; Liu, Changhua; Yu, Song; Hu, Xiaohang (Frontiers in Genetics, 2024)
Yellowhorn (Xanthoceras sorbifolium Bunge) is an oil-bearing tree species in northern China. In this study, we used yellowhorn from Heilongjiang to analyze the morphological and physiological changes of fruit development and conducted transcriptome sequencing. The results showed that the fruit experienced relatively slow growth from fertilization to DAF20 (20 days after flowering). From DAF40 to DAF60, the fruit entered an accelerated development stage, with a rapid increase in both transverse and longitudinal diameters, and the kernel contour developed completely at DAF40. From DAF60 to DAF80, the transverse and vertical diameters of the fruit developed slowly, and the overall measures remained stable until maturity. The soluble sugar, starch, and anthocyanin content gradually accumulated until reaching a peak at DAF80 and then rapidly decreased. RNA-seq analysis revealed differentially expressed genes (DEGs) in the seed coat and kernel, implying that seed components have different metabolite accumulation mechanisms. During the stages of seed kernel development, k-means clustering separated the DEGs into eight sub-classes, indicating gene expression shifts during the fruit ripening process. In subclass 8, the fatty acid biosynthesis pathway was enriched, suggesting that this class was responsible for lipid accumulation in the kernel. WGCNA revealed ten tissue-specific modules for the 12 samples among 20 modules. We identified 54 fatty acid biosynthesis pathway genes across the genome, of which 14 was quantified and confirmed by RT-qPCR. Most genes in the plastid synthesis stage showed high expression during the DAF40-DAF60 period, while genes in the endoplasmic reticulum synthesis stage showed diverse expression patterns. EVM0012847 (KCS) and EVM0002968 (HCD) showed similar high expression in the early stages and low expression in the late stages. EVM0022385 (HCD) exhibited decreased expression from DAF40 to DAF60 and then increased from DAF60 to DAF100. EVM0000575 (KCS) was increasingly expressed from DAF40 to DAF60 and then decreased from DAF60 to DAF100. Finally, we identified transcription factors (TFs)